Designing a Model for Teacher Competencies in Elementary Education - Bahmannia, Hengameh; Malaki , Hassan; Khosravi , Mahboubeh (Iranian Journal of Educational Sociology, 2022)
Purpose: Teacher competencies in the education system is among the most influential and important issues. This importance is rooted in the critical role of teachers in educating people in a society, because the more teachers are prepared and qualified, the greater their impact on upgrading the education system. Methodology: In this regard, upstream documents, as the most extensive strategic and guidance texts, have given much attention to the teacher competencies, with regard to their mission, including directing and drawing the ideal human and the pursuit of a pure life. This study was conducted aimed at presenting a model for the teacher competencies in elementary education based on upstream documents. For this purpose, three major activities were carried out. Initially, upstream documents were examined to identify the components and instances of the teacher competencies, and the opinions of experts in the field were also used. Then, the model of the teacher competencies was designed according to the extracted instances and components. The qualitative method was used in this study and documentary research method was also used to investigate the first question. Findings: In this method, all the upstream documents, including the document of fundamental transformation of education, the national document as well as the scientific documents and literature in this field, were carefully studied so that all explicit and implicit instances and components of teacher training are extracted. Moreover, semi-structured interviews were conducted to gain the viewpoints of the experts in order to achieve the representing themes of competencies through content analysis. Discussion: Finally, the model of professional competencies was designed on the basis of the teacher competencies developed in the previous stages to examine the second question.